2005
DOI: 10.1111/j.1365-277x.2005.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and clinical outcomes of older patients in rehabilitation

Abstract: Over half our sample was identified as at risk of malnutrition or malnourished and this was associated with poorer clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
79
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 26 publications
13
79
2
Order By: Relevance
“…physical function and quality of life in one study [35] and length of stay and poor 202 participation in rehabilitation activities in a second study [36]. However, a two further studies 203 found it was not able to predict length of stay, complications, physical function, 204 rehospitalisation, institutionalisation, discharge location or mortality [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…physical function and quality of life in one study [35] and length of stay and poor 202 participation in rehabilitation activities in a second study [36]. However, a two further studies 203 found it was not able to predict length of stay, complications, physical function, 204 rehospitalisation, institutionalisation, discharge location or mortality [21].…”
mentioning
confidence: 99%
“…However, two studies reported outliers, 0.06% in Australia [35] and 68% in Italy [50]. It is 286 unclear if these outliers in reported prevalence of malnutrition by the MNA are due to a real 287 difference in the severity of malnutrition in each study or due to possible differences in how 288 the tool was implemented.…”
mentioning
confidence: 99%
“…In the community, the prevalence of malnutrition in older adults aged 75-80 years is two-fold higher than the 65-74 age group (Ljungqvist et al, 2010). It is well-documented that malnourished older adults have higher mortality rates , reduced quality of life (Neumann et al, 2005), reduced ability to perform activities of daily living (Inoue and Kato, 2007;Izawa et al, 2014), risk of additional illness (BAPEN Malnutrition Advisory Group, 2003a) and they experience longer recovery times than wellnourished peers (BAPEN Malnutrition Advisory Group, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…A malnourished person is more likely to visit their General Practitioner (GP) and be admitted to hospital [4], where they have a longer stay [5][6][7], a higher rate of complications [5,6,8], and a slower functional recovery [7,9,10]. There is also an increased risk of hospital readmission [10,11] and mortality [12][13][14]. In 2011-12, malnutrition was estimated to cost the UK £19.6 billion [15].…”
Section: Introductionmentioning
confidence: 99%